Digital Nomad Work Trends in Indonesia After the Pandemic - Pramudya, Ardhani Wahyu Eka; Prasetyo, Handar Beni Dwi; Wempi, J. A. (International Journal of Science and Society, 2024)
After the Covid-19 epidemic, there has been a change in working style from people who are required to work from home to working from anywhere. Digital Nomad is a trend that has become popular in Indonesia since the government announced that people can work hybridly. This trend entered through Instagram social media, where tourists come and work in Bali, or what we know as Work from Bali. Seeing how this phenomenon has developed, it is now important to understand the application of digital nomads in post-pandemic Indonesia. This research uses interpretive qualitative methods so that researchers can interpret digital nomad trends, while data collection is carried out through document studies and literature studies. The results of this study show that the use of the digital nomad concept is growing in Indonesia, and many companies and government institutions are implementing remote working, thus supporting this trend to continue as long as we work digitally.